Asymptomatic Presentation of Aggressive Ossifying Fibroma:A Case Report - Roopashri Rajesh Kashyap; Gopakumar R. Nair; Subhas Babu Gogineni (Case Reports in Dentistry)
Ossifying fibromas form a part of the spectrum of fibro-osseous lesions of the jaws. They are rare, benign, nonaggressive tumors that are commonly seen in head and neck region. This paper presents the case of a 40-year-old female patient presented with minimal clinical symptoms, diagnosed to be suffering from aggressive form of ossifying fibroma of maxilla involving the maxillary sinus and ethmoid sinus. This paper emphasizes the importance of computed tomography in diagnosing such unapparent aggressive tumors.